Delivering information literacy skills in resource-based assignments through virtual school library/ Halida Yu, Saidatul Akmar Hj Ismail and Hussain Hashim - Yu, Halida; Ismail, Saidatul Akmar; Hashim, Hussain (Fakulti of Information Management, Universiti Teknologi MARA, 2015)
Resource-based school assignments have good potential to expose and guide school children on IL. IL integration through resource-based assignments is highly recommended these days. Delivering IL skills through resource-based assignments require collaborative efforts from both the subject teacher and the teacher librarian. A collaborative effort between the two parties is needed to design an all-encompassing assignment that will both improve students' subject-content mastery, as well as research and IL skills. Technology could play important role in assisting students to develop their IL skills, one of it is through virtual library services. Virtual library becomes increasingly important in providing reliable and updated information in inquiry-based learning environment.